Chemical Characterization, Cytotoxicity Studies and In vivo Anti-inflammatory Activities of Anti-cancer Plant: Rutidea parviflora (Rubiaceae) - Rosa, Johnson-Ajinwo Okiemute; Emmanuel, Udofia Cynthia; Godwin, Nyodee Dummene (Recent Developments in Medicine and Medical Research Vol. 3, 2021)
The rapid development of malignant cancers is characterized by inflammation, which poses a significant drawback in cancer therapy. Both cancer and inflammation operate on very similar mechanisms involving angiogenesis and cell proliferation. Currently, cancer-intrinsic inflammations have been shown to promote cancer progression and hinder apoptosis of cancerous cells. Thus, an effective strategy for chemoprevention and therapy would involve the control of inflammation. This research work aims to investigate the anti-inflammatory activity and cytotoxicity effects of the extracts of the root bark of Rutidea parviflora (Rubiaceae), (RP), a plant previously reported for anti-ovarian cancer activities and the isolation of palmatine; an anti-cancer compound and a second compound; urs-12-ene-24-oic acid, 3-oxo, methyl ester. This plant is renowned for its anti-inflammatory properties amongst locals in Delta state, Nigeria, which has necessitated this present research. Organic and aqueous extracts were obtained from the pulverized root bark by use of the America national cancer institute protocol (NCI). The organic extract was partitioned sequentially in increasing order of polarity with n-hexane, ethyl acetate, n-butanol and distilled water to obtain four fractions. Phytochemical screening using standard procedures and the Chemical characterization by GC-MS were undertaken. Results from the phytochemical screening indicated the presence of alkaloids, flavonoids, saponins, tannins, glycosides and carbohydrates. The GC-MS analysis identified the presence of a number of compounds of which Hexadecanoic acid, 10-hydroxy-,methyl ester, Octadecanoic acid and Eicosanoic acid were the most bioactive. Anti-inflammatory investigations of the extracts and fractions were carried out by the induction of inflammation. The animals were grouped into 12 test groups and 2 control groups with 6 rats per group. Egg albumin (0.1 ml) was administered sub-plantarly followed by treatment. Group A received a dose of 200 mg/kg of the plant extracts and Group B received a dose of 400 mg/kg of the plant extracts. Group C (positive control) received indomethacin (10 mg/kg), while Group D (negative control) received 1 ml of normal saline. Statistical analysis showed significance against the negative control indicated by P<0.05 for extracts and fractions. While for the fourth hour post induction of inflammation; the activities of the Group B organic extract, ethyl acetate and n-butanol fractions were comparable with indomethacin indicating that the plant possess significant anti-inflammatory activity. The Cytotoxicity studies carried out employed the Brine Shrimp (Artemia salina) Lethality Test (BSLT) and Allium cepa Cytotoxicity Assay (ACCA) methods. The results demonstrated that RP had minimal toxicity and thus had a very high safety profile. Thus the therapeutic use of this plant is highly recommended and warrants further anti-inflammatory studies.